Kerugian Terhadap Pemilik Sertifikat Akibat Pencatatan Blokir Sertifikat Hak Atas Tanah oleh Badan Pertanahan Nasional Tanjung Jabung Barat - Arsyani Hartawan, Frisca; Idris, Isran; Manik, Herlina (Universitas Jambi, Fakultas Hukum, 2024)
This research aims to identify and analyze the factors causing the blocking of land title certificates and the legal status of the holders of blocked land certificates. The research questions are as follows: 1) What are the factors causing the blocking of land title certificates?; and 2) What is the legal position of holders of blocked land certificates?. The research method used is an empirical juridical approach. Based on the research conducted, it was found that there are several main factors that can cause the improper blocking of land title certificates by the National Land Agency (BPN). These factors include a lack of understanding and awareness among BPN officials regarding rules and procedures, weak internal supervision within the BPN environment, insufficient socialization and training for BPN officials, unresolved land conflicts or disputes, pressures or interventions from certain parties, lack of transparency and accountability in the blocking recording process, errors in the application of rules and procedures, negligence or lack of thoroughness in land ownership data checks, and insufficient coordination and communication between BPN and other related institutions or agencies. The legal position of holders of improperly blocked land title certificates should be protected in accordance with applicable regulations. Holders of certificates acting in good faith have the right to control and utilize their land according to their rights. To ensure the legal position of certificate holders, the government needs to strengthen supervision of BPN actions, impose strict sanctions for violations, enhance legal protection through regulation revisions, improve transparency and accountability, and ensure effective and proportionate compensation mechanisms for affected certificate owners. The role of the judiciary, community participation, and commitment from all stakeholders are also crucial in safeguarding the legal position of holders of improperly blocked land title certificates.